1987
DOI: 10.1016/0014-5793(87)80526-4
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of melittin with negatively charged phospholipids: Consequences for lipid organization

Abstract: A characterization of the structural alterations induced by melittin in model-membranes of dioleoylphosphatidic acid and egg phosphatidylglycerol is presented, based on the use ofaxp-NMR, freeze-fracture electron microscopy and small angle X-ray scattering. In accordance with earlier findings on the cardiolipinmelittin system, melittin is found to have an inverted phase inducing effect on these negatively charged lipids, in contrast to the influence on zwitterionic phospholipids. In phosphatidic acid this is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
36
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 26 publications
10
36
0
Order By: Relevance
“…The stronger affinity of melittin for anionic than for neutral membranes had already been demonstrated [40][41]61 and is corroborated by the present results ( Figure 1). This preference for anionic membranes is likely due to attractive electrostatic interactions associated with the cationic residues of the peptide.…”
Section: Acs Paragon Plus Environmentsupporting
confidence: 92%
See 2 more Smart Citations
“…The stronger affinity of melittin for anionic than for neutral membranes had already been demonstrated [40][41]61 and is corroborated by the present results ( Figure 1). This preference for anionic membranes is likely due to attractive electrostatic interactions associated with the cationic residues of the peptide.…”
Section: Acs Paragon Plus Environmentsupporting
confidence: 92%
“…The titration curves indicated that melittin had a stronger affinity for negatively charged bilayers than for pure DPPC membranes; in the case of DPPC/DPPS 70/30 bilayers, the L/P 50 was shifted to 3.6 and ΔG bind was -30.5 kJ/mol. A consistent increased melittin affinity had already been reported for anionic membranes of PS, of phosphatidylglycerol (PG), or containing unprotonated palmitic acid (PA -) 41,59,61 . This enhanced attraction was proposed to be due to electrostatic interactions.…”
Section: Association To Luvssupporting
confidence: 71%
See 1 more Smart Citation
“…Both melittin (Dufourcq & Faucon, 1977) and human defensins interact strongly with negatively charged lipid bilayers. Lipid binding of melittin has also been reported to be enhanced (Batenburg et al, 1987) in the presence of the negatively charged lipids. The lipid-to-melittin ratios required to bind melittin completely (c 10 for negatively charged lipids at 100 mM saline, pH 7.3; Batenburg et al, 1987) is comparable to the value calculated by us for binding of human defensin HNP-1 (lipid/defensin = 20 mol/ mol at 100 mM saline, pH 7.4) to the D0PS:DPPC liposomes.…”
Section: Forces Involved In Defensin Destabilization Of Lipid Vesiclesmentioning
confidence: 99%
“…Whereas melittin disrupts PC bilayers into small structures, the peptides exhibit bilayer-stabilizing effects when mixed with phosphatidylethanolamine, a lipid with known tendency for inverse hexagonal phases (H II ) [134]. A different behavior is again observed when melittin is inserted into charged phospholipid membranes such as cardiolipin, 1,2-dioleoyl-sn-glycero-3-phosphatidic acid (DOPA) or egg-phosphatidylglycerol where the peptide induces inverted macroscopic phases (H II or cubic) [135,136]. Electrostatic interactions are not only important during membrane association of cationic amphiphiles, they also have a pronounced effect on the lateral distribution of lipids within the bilayer.…”
Section: Membrane Polymorphismmentioning
confidence: 95%